The death of the traditional workshop of Projects and the birth of the digital workshop of Architecture. - Espinoza., Felipe (Revista Universidad de Guayaquil, 2012)
The teaching of “Project Workshop” goes through a process where the old paradigms that used to be successful models over the past, face nowadays the need of revising the principles of their roots, considering that it is not just about adopting computer’s technology in order to replace the wood board, but updating their foundations, and confront new knowledge. Today, Le Corbusier, Wright and others are gone. The science of architectural space embraces environment, energy and its new multicultural ways of use. Discussion lays down the emergence of a new aesthetic, so we either get into the heart of the hurricane or stay outside, as it is shown by tests and results carried out in the Massachusetts Institute of Techonology (MIT) over the six strategic areas contained in its curriculum; Architecture Design, Building Technology, History, Theory and Criticism of Architecture and Art, Art, Culture and Technology (formerly Visual Arts)., Computation, and Environmental.
Keywords: Workshop; Paradigms; successful models; modernize technology; new knowledge; strategic areas; architectural solutions